TOURISM AND ITS STATISTICAL ASSESSMENT - Jumanova Zilola Tuychiyevna (Galaxy International Interdisciplinary Research Journal, 2022)
The article examines the impact of tourism on the socio-economic development of the country and topical problems of its assessment, studies the direct and indirect impact of tourism on the country’s economy.